AUGMENTING CLOUD-NATIVE TELECOM WITH HUMAN-AI PARTNERSHIP: ADVANCING AUTOMATION, SCALABILITY, AND SECURITY - Kavita Swapnil Kulkarni, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This article explores the transformative impact of human-AI partnerships in cloud-native telecommunications environments. The article examines how the integration of artificial intelligence with human expertise is reshaping key operational areas including automation, scalability, and security. Through a comprehensive analysis of industry implementations, the article demonstrates significant improvements in network management efficiency, threat detection capabilities, and predictive maintenance outcomes. The article reveals how human-AI collaboration enhances operational resilience while addressing implementation challenges through structured training programs and workforce development initiatives. It highlights the crucial role of balanced human oversight in maximizing AI system effectiveness, particularly in complex decision-making scenarios and strategic planning. This article contributes to the understanding of optimal integration strategies for human-AI partnerships in telecommunications infrastructure management.